Myth and the Schellingian Notion of Mythological Consciousness as a Basis of Narrative and Narrative Identity - Filutowska, Katarzyna 1975- (2014)
The paper concerns the problem of the mythological origins of narrative and narrative identity. Referring to works of such narrative researchers as D. Carr, B. Williams and K. Atkins and to F.W.J. Schelling’s conception of a mythological consciousness, I prove that 1. ina narration - personal as well as collective (in a tale which constitutes given culture) - the type of necessity is similar to that which occurs in nature as well as in mythology (its higher potential) and which is responsible for a perfect story coherence that is unavailable in normal life and characteristic rather of art than of a usual experience; 2. although our personal narratives are shaped on the basis of a collective myth, they assume a first-person, reflective perspective, and this is the reason why an individual may in spite of such to some extent “untrue” origins keep personal freedom and autonomy.
Keywords: świadomość mitologiczna; mit; Mitologia; narracja; tożsamość narracyjna